Telaah Kritis Tafsir Shi>’ah: Analisis Justifikasi Us}u>l Madhhab al-Shi>’ah dalam Interpretasi Ayat Al-Qur’an Mufassir Shi>’ah - Syariful Afif, Achmad Syariful Afif (MAGHZA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Interpretation of the Qur'an is oftenly become a land of contestation over scientific discourse, from fiqh to theology. So, there are times when the verses of the Qur'an are only used as a tool to legitimize a thought, whereas this is not allowed in the interpretation principles. Because of this, the experts formulated the al-as}i>l wa al-dakhi>l theory as a measuring tool (mi'ya>r) to examine various interpretations so that the distinction between a valid and weak interpretations become distinguishable, this theory can be used to analyze infiltration in interpretation, both in the form of narrative (bi al-ma'thu>r) and reason based interpretation (bi al-ra'yi). This article elaborates on the main doctrine of Shi>'ah (us}u>l madhab al-Shi'ah), such as the concept of al-ima>mah, 'is}mat al-ima>m, taqiyyah, al-mahdiyyah wa al-gaibah, al-raj'ah, al-z}uhu>r, al-bada' and 'aqi>dat al-t}i>nah and then traces its arguments in Shi'ah tafsir works. This material object is then communicated with its formal object, the theory of al-as}i>l wa al-dakhi>l. So, that this research aims to produce a classification of Shi>'ah tafsir based on its validity and prove if fanaticism can affect the authenticity of an interpretation. This research is a qualitative study based on literature review, so all the data comes from sources that are literature documents. This study shows that Shi'ah tafsir works such as the tasfir of Nu'ma>n b. H{ayyu>n, al-T{abarsi>, al-'Ayya>shi> and al-Qummi> in some places interprete verses to legitimize the opinions of their madhab, although for that they must use ta'wi>l fa>sid as well as problematic narratives which contradicts with the rules and principles of interpretation.